BALAI BENIH IKAN DI CENGKARENG - Jihand Setyani Rakafsya; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2020)
Technological advancements that were followed by millennial era made people start busy with their respective activities, while humans are social creatures who need each other and cannot live alone. The city began to congested along with its human growth, as if it were not allowed to rest. The skyscrapers and the density that piled up seemed to be a witness to the development of the city itself. People who are busy in their activities begin to lose time to rest for a moment, the density on the road and the route of the road that is passed every day starts to make people tired, bored, and often become stressed. This study aims to reduce the level of individualism in urban society with the role of architecture that can accommodate activities of chatting, with places that have an open system in general, safe, and comfortable without having to distinguish social strata. With the descriptive analysis design method,”Fish Farming in Cengkareng” tries to fill the third space for the West Cengkareng Village. Contribute to the government activities of the West Jakarta Office in improving the quality of freshwater ornamental fisheries production, and making it an open place for new people and enthusiasts of ornamental fish, making it an educational content and improving the local economy. Keywords: architecture; decorative fish; human; production; third place; troutAbstrakKemajuan teknologi yang diikuti oleh dominasi generasi milenial membuat manusia mulai sibuk dengan kegiatannya masing-masing, sementara manusia sendiri merupakan makhluk sosial yang saling membutuhkan dan tidak dapat hidup sendiri. Kota mulai padat beriringan dengan pertumbuhan manusianya, seolah-olah tidak diizinkan beristirahat. Gedung-gedung pencakar langit dan kepadatan yang menumpuk seolah menjadi saksi bagi perkembangan kota itu sendiri. Masyarakat yang sibuk dalam kegiatannya mulai kehilangan waktu untuk beristirahat sejenak. Kepadatan di jalan dan rute perjalanan harian yang setiap hari dilalui terasa membuat penat, bosan, dan tak jarang mengakibatkan stress. Studi ini bertujuan untuk mengurangi tingkat individualis dalam masyarakat kota dengan peran arsitektur yang dapat mewadahi kegiatan bercengkrama, dengan tempat yang memiliki sistem terbuka secara umum, aman, dan nyaman tanpa harus membedakan strata sosial. Dengan metode perancangan analisis deskriptif, “Balai Benih Ikan di Cengkareng” berusaha memenuhi ruang ketiga bagi Kelurahan Cengkareng Barat. Usulan proyek ini berupaya untuk memberikan kontribusi dalam kolaborasi kegiatan pemeritah Suku Dinas Jakarta Barat dalam meningkatkan kualitas produksi perikanan hias air tawar dan menjadikannya tempat terbuka bagi masyarakat umum atau penggemar ikan hias. Harapannya usulan proyek ini turut menjadi wadah edukasi serta peningkatan ekonomi daerah.